(untitled) (Indian Journal of Public Health Research & Development, 2022)
Background: There is an interdependency between thyroid hormones and renal function. Chronic Kidney Disease (CKD) is a degradation of renal function that is irreversible. Aimsand Objectives: To compare the thyroid hormone profiles of CKD patients receiving two distinct therapeutic approaches. Materials and methods: Over the course of one year, 200 newly diagnosed or known patients withCKD were recruited for a cross-sectional study. Group 1 consisted of 100 CKD patients treated conservatively, whereas Group 2 consisted of 100 CKD patients on haemodialysis. Fasting Blood Glucose (FBG), Serum urea (S. Urea), Serum Creatinine (S. Creatinine), and a thyroid hormone profile were all measured. Estimated Glomerular Filtration Rate (eGFR) was calculated using the Cockcroft-Gault formula. Results: The mean age of patients in Group 1 was 51.04 years and in Group 2 it was 53.20 years. S. Creatinine, S. Urea, and eGFR values changed significantly between the two treatment groups. In 36% of instances, a thyroid malfunction was present. Only FT4 differed significantly across the two groups (p = 0.026)Conclusion:Low levels of the thyroid hormones FT3, FT4, TT3, and TT4 were detected in all CKD cases. However, no significant differences in thyroid status were found between haemodialysis patients and non-dialysis patients.